ابن تيمية وحديث الغدير في منهج أهل السنة - عبد الرضا, باسم محمد; زاده, حسين مناحي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study examines Ibn Taymiyyah’s stance on Hadith al-Ghadir within the framework of Ahl al-Sunnah’s methodology in dealing with prophetic traditions related to Imamate and Caliphate. The research focuses on analyzing Ibn Taymiyyah’s critical perspective on the hadith and his interpretation of it within the theological dispute between Sunnis and Shiites. The study reviews the chains of narration of Hadith al-Ghadir and analyzes Sunni hadith scholars’ opinions on its authenticity. It then explores Ibn Taymiyyah’s interpretations, where he argued that the hadith does not indicate Imamate but rather love and support. The research examines Ibn Taymiyyah’s methodology in critiquing narrations and explains how he used the historical and political context to interpret the hadith away from its Imamic implications. The study compares Ibn Taymiyyah’s interpretation with other Sunni scholars' views and discusses Shiite scholars’ responses to his stance, assessing the strength of their arguments against his interpretation. It also examines the impact of Ibn Taymiyyah’s view on Sunni thought regarding Imamate and its relation to his general approach in rejecting interpretations that support the theory of divine designation in leadership. If Hadith al-Ghadir carries clear implications for Shiites, why did Ibn Taymiyyah adopt a different interpretation, and how has this influenced the Sunni perspective on Imamate?